Metodologia de curvatura de bambu laminado colado (BLAC) para fabricação de mobiliário: diretrizes para o design - Ramos, Bruno Perazzelli Farias [UNESP] (2014)
With the growing shortage of wood supply and the constant research to create environmentally freendly products, bamboo has been attracting increasing attention as a renewable raw material for the development of furniture. Being a material widely exploited in Eastern contries, where it presents a wide range of users, it is still unfamiliar and rarelly used in our country, requiring further studies for their proper development. For the manufacture of furniture with Glued Laminated Bamboo (GLB) it is noticed the necessity of producting curved pieces that can contribute with new possibilities in the area, however, threre is few literature about methods of making and using molds for this end. This research aims to develop a suitable methodology for the process of bending GLB pieces using using heated molds. To this end, first of all, a literature review was conducted about design issues, sustainability, bamboo, bamboo bending techniques and also laminate wood bending, since the information about the GLB bending are very scarce and laminated wood is the most singular material that can be used as reference. After the literature review, the harvesting of bamboo, the processing of the bamboo culms and the lamination, molds of the male-female type were made and an electric heating system for the molds was also developed. Experiments of gluing and pressing of the pieces of bended GLB were made and the pieces produced were analyzed by comparative templates with the objective of verifying the consistency of the results obtained, the variation of springback that occurred in the GLB pieces and the efficiency of the method used. At the end of the process, methodological guidelines were defined, that allows the technological development of the generation of curved of GLB and extends the possibilities of the use of bamboo as a material for furniture making